Efficacy of education strategies concerning organ shortage: state-of-the-art and proposals - Felix Cantarovich (Journal of Health and Social Sciences)
Introduction: Aim of this study was to review the underlying reasons for organ shortage and the efficacy of current education programs, in order to propose messages to modify socio-psychological feelings to donation. Discussion: Emotional barriers such as fear of death and mutilation are the major reasons for inadequate organ donation; nevertheless, education programs do not consider these barriers. Concerning non-cognitive factors as donation’s inhibitions, phrases ‘after death, our body is a unique source of health’ and ‘throughout life, we are potential recipients of a transplant’ should be suggestions for a slogan change. Youth education, starting early, should be well thought out to avoid irrational prejudice to donation. Educational curriculums should be globally established. Education and health stakeholders as well as religious authorities should support this strategy. In search to a long-term solution to the present crisis for society, this teaching strategy should be pedagogically adapted to the socioeconomic characteristics of each region. Conclusion: Educational options to improve knowledge and attitudes toward organ donation should be carefully planned to prevent ‘organ shortage’ becoming a permanent and unjustifiable critical health crisis.